Investigation of thermal performance in a solar air heater having variable arc ribbed fin configuration. (August 2022) - Sureandhar, G; Srinivasan, G; Muthukumar, P; Senthilmurugan, S
Graphical abstract: Highlights: Performance of solar air heater with variable arc ribbed arrangement was studied. Average outlet air temperature was reported between 55.1 °C and 60.5 °C. Maximum thermal (52.0%) and exergy (2.2 %) efficiency was achieved. Proposed air heater can be integrated with solar dryers to dry various products. Abstract: A solar air heater having arc ribbed wire configuration was designed and tested. The influence of variable arc ribbed fin arrangement on the performance of solar air heater (outlet air temperature, thermal, effective and exergy efficiency) was experimentally investigated. A solar air heater of length 2 m was embedded with arc ribbed wire of diameter 2 mm up to 0.5 m and 2.5 mm from 0.5 m to 2 m. The temperature variation of air inside the duct and absorber plate along the length was reported. The average outlet air temperature in a day was varied from 55.1 °C to 60.5 °C and the average temperature difference between inlet and outlet air temperature in the solar air heater was varied from 25.6 °C to 31.6 °C. The thermal efficiency (50.4 %), effective efficiency (49.8 %), and exergy efficiency (2.1 %) were maximum at 0.0175 kg s −1 . As the flow rate increases, the collector efficiency factor and heat removal factor were found to increase, whereas the total loss coefficient decreased. The proposed solar air heater's outlet temperature provides a favorable temperature range to dry various agricultural and food products, and hence, it can be integrated with various kind of solar dryers.